Unexpected formation of ansa isomers enabled by phosphazene ring flexibility in the reactions of cyclotetraphosphazene with 1,2-ethanediol - Palabiyik, Duygu; Mutlu Balci, Ceylan; Allen, Christopher W.; Besli, Serap (Royal Soc Chemistry, 2021)
In this work, the nucleophilic substitution reactions of the cyclotetraphosphazene, tetramer, (1) (N4P4Cl8) with the disodium salt of 1,2-ethanediol in THF solution at different mole ratios were demonstrated. Surprisingly, one double bridged (2) and three ansa derivatives [bis (3), tris (4) and tetrakis (5)] were formed demonstrating two competing pathways in these reactions. The new type cyclotetraphosphazene compounds (2-5) consisting of multiple rings were characterized by elemental analysis, mass spectrometry, H-1 and P-31 NMR spectroscopy and X-Ray crystallography. Although 1,2-ethanediol, a short chain diol, can only produce spiro type products with cyclotriphosphazene, (N3P3Cl6), it was able to give ansa type products with cyclotetraphosphazene which suggests the role of the ring flexibility of 1. Crystallographic evidence shows the distortion of the cyclotetraphosphazene ring.
Keywords: Substitution-Reactions; Crystal-Structure; Spiro; Derivatives; Ligands; Polyphosphazene; Chemistry